"It made me feel like I wasn't alone in the darkness": exploring dementia care network communication and coordination through a digital health platform. (27th September 2022) - Linden, Anna; Jolliff, Anna; Gonzalez, Deryk; Loganathar, Priya; Elliott, Christian; Zuraw, Matthew; Werner, Nicole E
Abstract: Objective: To explore the use of a shared communication and coordination platform—the CareVirtue journal feature—for care networks of people living with Alzheimer's disease and related dementias to inform the design of care network support technologies. Materials and Methods: In the primary study, care networks comprised the primary caregiver and other caregivers they invited to participate (eg, family members, in-home aides) used CareVirtue, for 60 days followed by a semistructured interview to explore primary caregivers' perceptions of usefulness. This secondary analysis focused on use of the shared journal feature of CareVirtue, which allowed care networks to communicate through posts that were shared with the network and to which network members could respond. Journal posts were analyzed using a deductive/inductive content analysis to categorize information behavior. We also conducted a thematic analysis of the interviews to identify primary caregivers' perceptions of the journal's usefulness. Results: Care networks used the journal for: (1) information acquisition, (2) information sharing, (3) strategy development, and (4) information feedback. Thematic analysis revealed that caregivers felt the journal was useful at the individual, care network, and relational levels and that journal integration was influenced by care network structure and relationships. Discussion: Care networks used the journal to document, share, and acquire information; co-create strategies; and provide support. The usefulness of this shared communication and coordination platform included individual and care network level benefits. Conclusion: These findings point to the importance of caregiver-centered technologies that support both the individual primary caregiver and the care network.